Maternal Knowledge and Husband Support in Antenatal Education Classes: Pengetahuan Ibu dan Dukungan Suami dalam Kelas Pendidikan Antenatal - Fachrudin , Moch Erfan; Sukmana, Hendra (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Maternal and neonatal mortality remains a national health concern in Indonesia. Education through the Kelas Ibu Hamil program is designed to improve pregnant women’s knowledge and family preparedness for childbirth. Specific Background: This study analyzes the implementation of maternal education at community health centers (puskesmas) to understand its contribution to maternal awareness and behavioral changes. Knowledge Gap: Although the program is widespread, variations in delivery methods, participation rates, and spousal involvement remain underexplored. Aims: To evaluate the relationship between maternal characteristics, class participation, and family support in improving pregnancy care knowledge. Results: The findings reveal that participation in Kelas Ibu Hamil enhances mothers’ understanding of antenatal care, nutrition, and childbirth preparation. Inclusion of husbands increases maternal confidence and promotes healthy behaviors during pregnancy. Novelty: The study presents evidence of the synergistic role of maternal and paternal involvement in community-based antenatal education. Implications: Findings support the expansion of family-centered antenatal education models to improve maternal and neonatal health outcomes in Indonesia. Highlights:• Maternal education improves antenatal knowledge and behavior• Husband participation strengthens health preparedness• Family-centered learning enhances maternal confidence